The Influence of Price and Product Quality on Consumer Satisfaction at Rantauprapat Homesmart - Alvira Rahmi; Bayu Eko Broto; Fauziah Hanum (PT Mattawang Mediatama Solution, 2022)
This study was conducted to determine and analyze the effect of price, product quality on consumer satisfaction. Price (X1) is the amount of value that consumers exchange for a product or service that has benefits when consumers have or use the product or service. product quality (X2) is the ability of the product to meet or satisfy the needs and desires of consumers. Consumer satisfaction (Y) is something that is sought to meet the needs needed. The design of this study is hypothesis testing using primary data obtained by distributing 100 questionnaires to consumers of HomeSmart RantauPrapat. The measuring scale used is the Likert scale. The data analysis technique used is the multiple linear regression analysis technique of quantitative data using the Statistical Sciences Package for the Social Sciences (SPSS) statistical method. The results of this study conclude that partially there is a significant and positive effect between price and product quality, simultaneously the same thing also occurs, namely a significant and positive effect between satisfaction, price and product quality on consumer satisfaction.